THE IMPLEMENTATION OF AN INDEPENDENT LEARNING CURRICULUM ON THE INFLUENCE OF STUDENT LEARNING OUTCOMES IN HISTORY SUBJECTS - Kakilo, Tiara Anggriayani; Yunus, Resmiyati; Mondong, Tonny Iskandar (Satmata: Journal of Historical Education Studies, 2024)
This research aims to investigate the influence of the Merdeka Belajar curriculum implementation on students' learning outcomes in the history subjeet. This research uses a quantitative approach. The results of the research show that respondents have not faced significant issues in implementing the Merdeka Belajar Curriculum. Respondents generally express enthusiasm and eagerness towards the implemented learning, methods. This indicates that the more flexible and student-centered approach in the Merdeka Belajar Curriculum has improved the students' learning outcomes. Overall, although the implementation of the Merdeka Belajar Curriculum is viewed positively and successfully motivates students to improve their learning outcomes, it is crucial for the teachers to continuously gather feedback and adapt their approaches so that all students can follow along and feel comfortable in the learning process.